Developing comprehensive resilient water systems and their driving factors for the 21st Century Society in China. Issue 1 (1st October 2022) - Yang, Jingwei; Xue, Fei; Sun, Xiang; Luo, Yao; Wang, Jian
Abstract: More frequent and severe natural disasters triggered by climate change and the increasing domestic water consumption have placed higher demands on sustainable water services. The establishment of "Resilient Cities" provides overall guidance on future directions of water affairs. Literature reviews were designed to transform the concept of resilient cities into waterworks from the dimensions and properties. Then the concept of "Resilient Water Affairs" was put forward. Evaluation indicators of resilient water affairs were summarized based on dimensions and properties to indicate the driving factors of the resilient water system. Finally, the future trends of resilient water affairs were proposed, which provides theoretical and technical support for establishing resilient water affairs.